2013
DOI: 10.1007/s11248-013-9718-3
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic approach to study the mechanism of tolerance to Bt toxins in Ostrinia furnacalis larvae selected for resistance to Cry1Ab

Abstract: A Cry1Ab-resistant population of Asian corn borer (ACB-AbR) exhibiting approximately 100 times greater resistance to activated Cry1Ab than a susceptible population (Ostrinia furnacalis; ACB-BtS), was previously shown to exhibit high levels of cross-resistance to Cry1Ah (131-fold), but no cross-resistance to Cry1Ie. It was suggested that the proposed mechanism of resistance was due to the alteration of specific receptors for Cry toxins in the midgut brush border membrane. In the present study a proteomic-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…It was found that a transgenic maize line expressing cry1Ie was highly resistant against the stem borer O. furnacalis [24]. In addition, it appears that the Cry1Ie protein has no cross-resistance with other Lepidoptera-active insecticidal proteins such as Cry1Ab, Cry1Ac, Cry1Ah, or Cry1F [25,26,27], making it a suitable candidate gene for developing stacked events for improved pest control. However, our knowledge regarding the potential effects of the Cry1Ie protein on non-target beneficial arthropods is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that a transgenic maize line expressing cry1Ie was highly resistant against the stem borer O. furnacalis [24]. In addition, it appears that the Cry1Ie protein has no cross-resistance with other Lepidoptera-active insecticidal proteins such as Cry1Ab, Cry1Ac, Cry1Ah, or Cry1F [25,26,27], making it a suitable candidate gene for developing stacked events for improved pest control. However, our knowledge regarding the potential effects of the Cry1Ie protein on non-target beneficial arthropods is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the mode of action underlying Cry toxin interactions with their hosts is critical for elucidating the molecular basis of toxin specificity and facilitating the development of new pest management tools. V‐ATPase has been identified as a Cry toxin‐binding protein in Heliothis virescens (Cry1Ac), Helicoverpa armigera (Cry1Ac) and Ostrinia furnacalis (Cry1Ab) (Krishnamoorthy et al ., ; Chen et al ., ; Xu et al ., ). Our previous studies suggest that V‐ATPase subunits A and B are Cry2Aa toxin‐binding proteins in Spodoptera exigua (Qiu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…V‐ATPases are located in the goblet cell apical membrane, which is involved in energy production and conversion (Nishi and Forgac, ; Beyenbach and Wieczorek, ). Evidence from a number of studies appears to indicate a role for V‐ATPase in the toxicity of Cry proteins in susceptible insects (Krishnamoorthy et al ., ; Chen et al ., ; Nakasu et al ., ; Contreras et al ., ; Xu et al ., ; Zhou et al ., ). The potential role of the V‐ATPase subunit A in mediating the toxicity of Bt Cry toxins in C. suppressalis has not previously been examined.…”
Section: Introductionmentioning
confidence: 99%
“…V-ATPase up-regulation has been found to be related to Cry1Ac resistance in Plodia interpunctella and P. xylostella 3031. Although V-ATPase has been identified as a Cry toxin-binding protein in H. virescens (Cry1Ac), H. armigera (Cry1Ac) and O. furnacalis (Cry1Ab)323334, little is known about its function with regard to Cry toxins in other insects. Interestingly, RNA silencing of the A. aegypti ATP synthase subunit beta increased larval mortality to Cry toxins, which suggests that this protein is involved in Cry toxin resistance35.…”
Section: Discussionmentioning
confidence: 99%